​​Does ESG Performance Affect the Cost of Debt? A Multi-Model Analysis Incorporating Debt Maturity, ESG Data Sources, and Moderating Governance Signals​ - Chhipa, Bhavini (Cranfield University, 2025)
This article examines how environmental, social and governance (ESG) performance influences the cost of debt for publicly listed firms in Europe between 2012 and 2023. Drawing on data from both Refinitiv and Bloomberg and using composite and pillar‑level scores to limit provider bias, we estimate fixed‑effects regressions, two‑stage least squares (2SLS) models and dynamic system generalised method of moments (GMM) to address endogeneity and path dependence. Our results show that static models associate higher ESG scores with higher borrowing costs, suggesting creditors view sustainability expenditure as an immediate cost. By contrast, dynamic GMM models reveal that lagged ESG performance reduces the cost of debt substantially, implying that reputational and risk‑mitigating benefits accrue over time (Cheng et al., 2014; Flammer, 2021). Pillar analyses demonstrate that social performance consistently lowers borrowing costs, while environmental and governance effects are sensitive to the estimation method: environmental initiatives increase borrowing costs in static models but become beneficial under GMM, whereas governance initiatives raise costs across all specifications. Moderation analyses indicate that transparent CSR reporting and audit independence amplify ESG’s benefits, whereas state ownership and large firm size weaken them. Robustness checks using a sovereign spread proxy confirm that the results are not an artefact of the accounting measure. These findings highlight the dynamic, dimension‑specific and context‑dependent nature of ESG’s financial materiality and offer practical insights for managers, creditors and policymakers.
Keywords: ESG performance; Cost of debt; Europe; Corporate governance; Dynamic panel; Sustainable finance; Financial materiality